A study of factors associated with strokes in young adults in Hospital Universiti Sains Malaysia,Kelantan - Nurfizan Azmi, Azrianna (2014)
Background Stroke in young adults causes morbidity and it is responsible for significant socioeconomic losses worldwide. There are limited data regarding the incidence and prevalence of strokes in Malaysia. A prospective, hospital-based study concluded that large vessel atherosclerosis and small vessel occlusion are the most common types of strokes. Diabetes, hypertension and chronic renal disease were found to be significant risk factors for young ischaemic stroke. The objective of this study was to determine the association between risk factors and ischaemic strokes in young adults. Information regarding the factors associated with ischaemic stroke in young adults in a local setting would improve our quality of care and it might provide ways to reduce the incidence of such strokes. Methodology This is a retrospective cohort study of 166 young adult patients which 99 of suffered an ischaemic stroke, and 67 of which suffered a non ischaemic stroke. The variables included in this study were hypertension, diabetes mellitus, dyslipidemia, smoking, alcohol intake, ischaemic heart disease, valvular heart disease, atrial fibrillation and previous ischaemic stroke. Data were assessed using simple logistic regression analysis to look for associations with ischaemic strokes and large artery atherosclerosis. Any factors with a P value ≤ 0.25 were included in the multiple logistic regression analysis and P value ≤ 0.05 were considered to be significant. Result The mean/±SD age for ischaemic stroke patients was 38.6 (±4.96). Hypertension was found to be associated with young ischaemic stroke (OR=1.85, 95% CI: 3. 10, 12.98, p<0.001) and diabetes mellitus was associated with large artery atherosclerosis in young ischaemic stroke patients. (OR=1.63, 95%CI: 1. 86, 13.94, p=0.002). Conclusion This study showed that hypertension is significantly associated with ischaemic stroke and that diabetes mellitus was associated with large artery atherosclerosis in young adults. Optimal management of hypertension and diabetes mellitus in young patients is recommended to reduce the risk of stroke and to prevent significant morbidity and mortality in these patients.